Peranan Sekuent Cartigram Pada Pemeriksaan MRI Knee Joint Dengan Kasus Anterior Cruciate Ligament DI Instalasi Radiologi RSUD Sidoarjo - Moh Rivaldi Lantang; A.A Aris Diartama; Triningsih Triningsih (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Background: The MRI knee joint examination procedure for clinical ACL rupture in the Radiology Installation of Sidoarjo Regional Hospital often adds a T2 Mapping MR Cartigram sequence. T2 mapping MR Cartigram is a special sequence for detecting damage to the collagen component of the cartilage matrix using a quantitative approach method by producing a color map. The aim of this research is to determine the procedure, reasons for use, and diagnostic information resulting from the T2 mapping MR Cartigram sequence. Method: This type of research is qualitative research with a case study approach. The research was conducted in March-June 2022 at the Radiology Installation of Sidoarjo Regional Hospital. Research subjects included three patients, three radiographers, one radiologist, and one sending doctor. Data was collected by means of observation, interviews and documentation and then analyzed using an interactive model system method which would be processed in the form of transcripts, then identified, reduced and categorized the data and made open coding so that conclusions could be drawn. Results: The results of the study show that the clinical MRI knee joint examination procedure for ACL rupture at Sidoarjo District Hospital includes patient preparation, equipment preparation, examination techniques and routine sequences used such as PD Fatsat, T2, T1, STIR, T2*GRE, PD 3D Cube, and additional T2 Mapping MR Cartiram sequence. The use of the T2 mapping MR Cartigram sequence aims to determine the effect of ACL rupture on cartilage damage quantitatively and objectively by placing an ROI in the cartilage area so that it can provide diagnostic information including early detection of cartilage damage, increased water content, and cartilage degenerative processes. The results of the interpretation of the analysis carried out by the Sidoarjo Regional Hospital Radiologist were only subjective, namely looking at the resulting color map to see whether it looked even and homogeneous. Conclusion: Basically, existing saturation measurements are not always the same, they will depend on the patient's diagnosis for which the action will be taken. This saturation measurement uses the AVOXimeter 1000E. no less important in the continuity of actions in the cath lab room.